Acid Ferric Sulfate Leaching of Attritor-Ground Chalcopyrite Concentrates - L. W. Beckstead (The Minerals, Metals and Materials Society, 1976)
The use of acid ferric sulfate solution as a lixiviant for chalcopyrite concentrates has been of little interest from a practical standpoint due to the formation of a tenacious layer of elemental sulfur which severely impedes the reaction progress. CuFeS2 + 4Fe+3 ?Cu+2 + 5Fe+2 +2s° For example, an acid ferric sulfate leach of chalcopyrite concentrate results in only 12% copper extraction in a three hour leach at 93°C. Experimental results suggest that particle size is the only controllable variable which has a significant effect on the rate of acid ferric sulfate leaching at ambient pressure. Size reduction of the concentrate prior to leaching was exam¬ined using various methods of grinding. Of the grinding methods considered, attrition grinding was found to be the most effective. Leaching of an attritor-ground product (median particle size 0.5 microns) resulted in approximately 90% copper extraction in a three hour leach at 93°C. Energy measurements suggest that the costs associated with attrition mill¬ing are not unreasonable. Evidence indicates that "activation" or stored strain energy is not responsibile for the enhanced reaction kinetics of the finely ground concentrate, but rather the experimental results can be explained simply in terms of the increased surface area due to size reduction. Leaching reaction mech¬anisms operative in the acid ferric sulfate system are discussed and the application of ultra-fine grinding technology to other systems is considered.